Product of independent random variables involving inverted hypergeometric function type I variables (2009)
The type I inverted hypergeometric function distribution has the probability density function proportional to [formula] where 2F1 is the Gaussian hypergeometric function. In this article, the product probability density function is derived from two independent random variables that are distributed according to the inverse hypergeometric type I function. Other products are also considered among random variables with beta distribution type I, beta type II, beta type III , hypergeometric function type I, inverse hypergeometric function type I and Kummer – beta.